Penerapan Model Pembelajaran Berdeferensiasi dengan Model Discover Learning dapat Meningkatkan Hasil Belajar PPKn pada Peserta Didik Kelas X.3 SMA Negeri 6 Kabupaten Maros - Abdul Afif; Muhammad Risal; Haeril Herisal; Abdul Rahman Rahim (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This study aims to explore the effect of applying differentiated learning model with Discover Learning model on learning outcomes of Pancasila and Civics Education (PPKn) in class X.3 SMA Negeri 6 Maros Regency. The research method used was classroom action research (PTK) with a double cycle design. The research participants consisted of 28 students of class X.3 SMA Negeri 6 Maros Regency consisting of various ability levels. Learning outcome data were collected through tests and observations. The results showed that the application of differentiated learning model with Discover Learning model can improve Civics learning outcomes in students of class X.3 SMA Negeri 6 Maros Regency. There were significant improvements in concept understanding, critical thinking skills, and learning motivation of learners after the application of this learning model. This finding shows that the use of differentiated learning model with Discover Learning model can be an effective alternative in improving Civics learning outcomes in students of class X.3 SMA Negeri 6 Maros Regency.